Plasmacytoid Dendritic Cells Respond Directly to Apoptotic Cells by Secreting Immune Regulatory IL-10 or IFN-α - Simpson, Joanne; Miles, Katherine; Trüb, Marta; MacMahon, Roisin; Gray, Mohini (Frontiers in Immunology, 2016)
Plasmacytoid dendritic cells (pDCs) play a pivotal role in driving the autoimmune disease systemic lupus erythematosus, via the secretion of IFNα in response to nuclear self-antigens complexed with auto-antibodies. Apoptotic cells, generated at sites of inflammation or secondary lymphoid organs, are exposed to activated pDCs and also express the same nuclear antigens on their cell surface. Here we show, that in the absence of autoantibodies, activated pDCs respond to apoptotic cell expressed chromatin complexes by secreting IL-10 and IL-6, which also induces T cells to secrete IL-10. Conversely, when activated by the viral mimetic, CpGA, apoptotic cells enhance their secretion of IFNα. This study demonstrates, that activated pDCs respond directly to apoptotic cells and may maintain tolerance via IL-10, or promote inflammation through secretion of IFNα, depending on the inflammatory context.